2018
DOI: 10.1002/ps.4883
|View full text |Cite
|
Sign up to set email alerts
|

Does mating disruption of Planococcus ficus and Lobesia botrana affect the diversity, abundance and composition of natural enemies in Israeli vineyards?

Abstract: Non-target effects of MD involved mostly A. sp. nr. pseudococci females and hardly affected other natural enemies. These findings support the use of MD as an environmentally friendly pest management strategy. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Since then, a number of commercial products for Pl. ficus MD have been tested worldwide, including in Tunisia [ 50 ], Israel [ 51 , 52 ], and Italy [ 53 , 54 ]. Here, we describe the initial Pl.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of commercial products for Pl. ficus MD have been tested worldwide, including in Tunisia [ 50 ], Israel [ 51 , 52 ], and Italy [ 53 , 54 ]. Here, we describe the initial Pl.…”
Section: Introductionmentioning
confidence: 99%
“…This kairomonal response of the parasitoid may contribute to enhance biological control of the VMB in MD conditions. In fact, in most of the cases, the level of parasitism of the VMB has been reported to be higher in MD plots compared to control (Walton et al 2006;Cocco et al 2014;Shapira et al 2018). However, the higher parasitism level observed in MD plots may be also related with the higher longevity of VMB females, which are thus expected to be exposed to parasitisation for a longer period.…”
Section: Mechanisms Explaining the Effectiveness Of Mating Disruption...mentioning
confidence: 94%
“…In fact, experiments showed no significant differences, in the level of parasitisation of VMB by A. vladimiri, between MD and control vineyards (Walton et al 2006), or even an increase of parasitism level in pheromone-treated plots (Daane et al 2006;Cocco et al 2014), suggesting that MD does not disrupt parasitism or may even enhance it. More recently, Shapira et al (2018) tested whether the use of MD to control the VMB and L. botrana affects hymenopteran parasitoids and spiders in wine-producing vineyards in Israel. The results showed that MD did not influence the abundance, diversity and community composition of most parasitoids and spiders.…”
Section: Compatibility Of Mating Disruption With Biological and Chemi...mentioning
confidence: 99%
“…Among these, spurge flax, Daphne gnidium L. (Thymelaeaceae), very likely represents its originary wild host plant [ 30 , 31 , 32 , 33 ]. Several studies focused on the parasitoid complex of EGVM in the European vineyards [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], but very little is still known about parasitoids developing on wild EGVM populations [ 32 , 59 , 60 , 61 , 62 , 63 , 64 ]. In this scenario, we investigated the community structure of EGVM parasitoids on D. gnidium in a wild area where grapevine is absent, during a three-year sampling.…”
Section: Introductionmentioning
confidence: 99%